ISLAMIC LEGAL PHILOSOPHY : ETHICAL BASIS IN CORPORATE SOCIAL RESPONSIBILITY PRACTICES IN THE BUSINESS - Radityo, Eka; Disantara, Fradhana Putra; Geraldha Islami Putra Disantara (Ajudikasi : Jurnal Ilmu Hukum, 2024)
The research aims to explore and analyze how Islamic legal philosophy principles can serve as a comprehensive ethical foundation in implementing Corporate Social Responsibility (CSR) to encourage meaningful and empowering business practices. This research uses normative legal research methods with conceptual and normative approaches, examining primary, secondary, and tertiary legal sources through literature study, to analyze Islamic legal philosophy principles as an ethical foundation in CSR practices. The research findings reveal that Islamic legal philosophy principles can serve as a comprehensive ethical foundation for Corporate Social Responsibility through a holistic approach integrating economic, social, and spiritual interests. Islamic values such as maqashid al-shari'ah, justice, trust, and social responsibility encourage companies to transcend financial profit orientation towards community empowerment and environmental preservation, emphasizing the balance between worldly and spiritual obligations. The implementation of Islam-based CSR not only creates harmonious relationships between companies and society but also supports global sustainable development agendas through ethical, transparent business practices with multidimensional positive impacts, thereby transforming CSR from a mere legal obligation into a meaningful instrument of social transformation..